2021
DOI: 10.1145/3478107
|View full text |Cite
|
Sign up to set email alerts
|

OpiTrack

Abstract: Opioid use disorder is a medical condition with major social and economic consequences. While ubiquitous physiological sensing technologies have been widely adopted and extensively used to monitor day-to-day activities and deliver targeted interventions to improve human health, the use of these technologies to detect drug use in natural environments has been largely underexplored. The long-term goal of our work is to develop a mobile technology system that can identify high-risk opioid-related events (i.e., de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 86 publications
0
1
0
Order By: Relevance
“…Since that study was published, there have been technological developments in this area to meet the pressing need that arose during the COVID-19 pandemic. Specifically, new wearable sensors have been developed that monitor sweat, heart rate, and temperature and that predict overdose in patients [7][8][9][10][11][12][13]. Several studies have evaluated the application of wearable opioid sensors for detecting overdose by detecting changes in temperature, movement, respiratory rate, heart rate, and electrodermal activity [8,[11][12][13][14][15][16][17].…”
Section: Overviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Since that study was published, there have been technological developments in this area to meet the pressing need that arose during the COVID-19 pandemic. Specifically, new wearable sensors have been developed that monitor sweat, heart rate, and temperature and that predict overdose in patients [7][8][9][10][11][12][13]. Several studies have evaluated the application of wearable opioid sensors for detecting overdose by detecting changes in temperature, movement, respiratory rate, heart rate, and electrodermal activity [8,[11][12][13][14][15][16][17].…”
Section: Overviewmentioning
confidence: 99%
“…Specifically, new wearable sensors have been developed that monitor sweat, heart rate, and temperature and that predict overdose in patients [7][8][9][10][11][12][13]. Several studies have evaluated the application of wearable opioid sensors for detecting overdose by detecting changes in temperature, movement, respiratory rate, heart rate, and electrodermal activity [8,[11][12][13][14][15][16][17]. Most of the studies involved a wrist-worn biosensor, usually the Empatica E4 biosensor and Q sensor, which integrate a machine learning algorithm.…”
Section: Overviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Machine learning, which analyzes patterns in large datasets to build predictive models, may be useful in this pursuit. Prior work has already demonstrated that modeling wearable sensor data with a temporal convolutional neural network can detect opioid use (Gullapalli et al, 2021 ). Hypothetically, a machine learning model can analyze underlying patterns in physiological signals passively recorded during a specific mindfulness session to predict the effectiveness of the session.…”
mentioning
confidence: 99%